Exploring belonging through photovoice: examining the impact of space design on diverse student populations in an academic library - Poljak, Leslie; Webster, Berenika M.; Kiner, Renee (Performance measurement and metrics, 2023)
PurposeThis paper aims to uncover characteristics of physical spaces that evoke feelings of welcome and belonging in a diverse student population in an academic library.Design/methodology/approachThe photovoice method was used to allow research participants an active role in shaping research questions and collecting and analyzing data.FindingsThe research reveals that space design significantly influences students' feelings of physical safety, emotional well-being and safety and ownership (or sense of belonging) in academic library spaces, thereby emphasizing the importance of considering space design in promoting student well-being and inclusiveness.Originality/valueThis research used photovoice methodology to engage underrepresented student communities in providing input into the design of library spaces.